Youth and media participation: key issues of concern - Shiratuddin, Norshuhada; Hassan, Shahizan; Ahmad, Mohd Khairie; Abd Rahman, Nurul Labanihuda (IRAJ, 2016)
The importance of youth participation in decision making process in nation building should not be underestimated.Studies have shown that youth in the marginalized communities have lack of opportunities to get engaged in a democratic process.However, the advent of media technology provides an opportunity for the authority to tackle this problem. Henceforth, how participation of youth who are at risk in the marginalized communities can be increased through the use of media is undertaken.To measure the media participation among youth, focus groups were conducted to investigate the issues preferred to be engaged by the youth, the contents to be produced as participation manifestation while exploring youth web based skills.The findings indicate that there are three issues to be highlighted which are economy political and social issues. n exploring the youth participation, a website for youth, called Y4M: youth for Malaysia, which has three main web broadcasting sub-menus: web tv, web radio, and web journalism is produced as a gateway for the youth to voice their opinions.